A quasi-experimental intervention study : effectiveness of reading strategy based instruction with adolescents - Özge, Razi (Trinity College (Dublin, Ireland). School of Education, 2013)
The study was designed as a quasi-experimental intervention study. There were two intervention groups and two control groups, with 119 students in total. A set of strategies corresponding to reading factors presented in literature was incorporated into the Strategy Based Instruction. The intervention group students attended SBI for 80 minutes each week for 16 weeks. The aim of the SBI was teaching students to use reading strategies in clusters in order to increase their reading comprehension. This aim was achieved by employing a SBI with two sequential phases. The first phase was used to introduce new strategies in a step by step manner. During the second phase students practised using the reading strategies that they had learned in the first phase, and experienced combining strategies in clusters. Each lesson was conducted with a self-evaluation stage in which students discussed the usefulness of strategies.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin